2007
DOI: 10.4049/jimmunol.178.2.1002
|View full text |Cite
|
Sign up to set email alerts
|

lgtC Expression Modulates Resistance to C4b Deposition on an Invasive Nontypeable Haemophilus influenzae

Abstract: We have previously shown that C3 binding to serum-resistant nontypeable Haemophilus influenzae (NTHi) strain R2866 is slower than C3 binding to a serum-sensitive strain. Ab-dependent classical pathway activation is required for complement-dependent killing of NTHi. To further characterize the mechanism(s) of serum resistance of R2866, we compared binding of complement component C4b to R2866 with a serum-sensitive variant, R3392. We show that C4b binding to R2866 relative to R3392 was delayed, suggesting regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 40 publications
1
39
1
1
Order By: Relevance
“…By using two independent methods, we showed that most of the NTHi strains bound C4BP, whereas the majority of the typeable strains did not. This finding is in contrast to a recent study, in which no binding of H. influenzae to C4BP was found (46). However, this study focused on one particular strain of NTHi: R3392.…”
Section: Discussioncontrasting
confidence: 55%
“…By using two independent methods, we showed that most of the NTHi strains bound C4BP, whereas the majority of the typeable strains did not. This finding is in contrast to a recent study, in which no binding of H. influenzae to C4BP was found (46). However, this study focused on one particular strain of NTHi: R3392.…”
Section: Discussioncontrasting
confidence: 55%
“…Phase variation of outer membrane proteins and lipooligosaccharides also contributes to virulence of H. influenzae and is involved in evasion of the immune system (39). Intriguingly, phase variation can affect binding of regulatory proteins and has been shown to affect serum resistance (19). Since phase variation is a common phenomenon and depends on the current bacterial environment, it cannot be excluded that phase variation is a factor affecting the in vitro results of our study.…”
Section: Vol 48 2010mentioning
confidence: 49%
“…Importantly, no significant difference in survival between the various clinical strains from blood samples and those from nasopharynxes was found when serum resistance was determined, suggesting the need for NTHi, irrespective of isolation site, for resistance of bactericidal activity of human serum. Previous studies showed that the NTHi strain R2866, which was isolated from a child with meningitis, had a high degree of serum resistance depending on the expression of the lipooligosaccharide biosynthesis gene lgtC (9,19,40). The phase-variable lgtC expression was demonstrated to inhibit C4b deposition and render the bacteria more resistant to human serum (19).…”
Section: Vol 48 2010mentioning
confidence: 99%
See 1 more Smart Citation
“…The lic2A and lgtC genes were nearly ubiquitous in H. influenzae (Ն90%) but were only 16 and 2% prevalent, respectively, in H. haemolyticus. Interestingly, the combined expression of these genes in H. influenzae is necessary to form a LOS digalactoside structure (34,35) that antigenically mimics the pK blood group of humans and increases the serum resistance of the organism by inhibiting the deposition of the C4b released from the classical complement pathway (21,61). Of the 17 H. haemolyticus strains in this study that possessed a lic2A gene, none possessed the lgtC gene (unpublished data), suggesting that the digalactoside structure is not made in H. haemolyticus.…”
Section: Discussionmentioning
confidence: 99%